‘Terentius cum figuris’ (preliminari a una ricerca) - Piermario Vescovo (Drammaturgia, 2017)
Notoriously, Terence’s comedies are the only tradition that comes from ancient times, through the centuries, accompanied by a set of images. Drawing the lines of a wider research, the essay suggests that the first modern edition cum figures (Lyon 1493) funds his project and his ‘comments for images’, which accompanies the commentary of words, on the late ancient tradition. In this perspective, the transmission and interpretation of elements of material culture of the ancient theater take on a different meaning, offered and turned across the images.